MODEL FOR THE FORMATION OF A PROJECT TEAM COMPOSITION BASED ON DISCRETE OPTIMIZATION METHODS - S.M. Beketov; M.V. Dergachev; S.G. Redko (Модели, системы, сети в экономике, технике, природе и обществе)
Background. The research is devoted to the development of a model for the formation of optimal team composition for projects in general, and for innovative ones in particular, which are the basis of economic progress in the modern information society. The problem lies in the need to improve the efficiency and effectiveness of projects by optimizing the composition of teams. The aim of the study is to create a mathematical model for the formation of project teams, taking into account factors such as qualifications, productivity and innovative potential of participants. Materials and methods. The methodological and instrumental basis of the research was made up of general scientific and special optimization methods, the basics of cybernetics, and mathematical modeling. Results. The paper examines existing approaches to team building and develops an algorithm that minimizes personnel costs while maintaining high efficiency. The practical application of the model is demonstrated by the example of IT projects, which shows the possibilities of optimizing human resources and increasing productivity. The model ensures the optimal composition of the project team, which in turn contributes to the economic progress of project-oriented enterprises. Conclusions. The research is aimed at improving project management methods and models and may be useful for project managers, HR specialists and company management seeking to implement methods to optimize the composition of teams in the implementation of projects. The implementation of the developed model can help to increase the predictability and manageability of projects, which is especially important in the context of the growing complexity and scale of modern projects.